Processes of Stroke Unit Care and Outcomes at Discharge in Vietnam: Findings from the Registry of Stroke Care Quality (RES-Q) in a Major Public Hospital. Issue 2 (December 2019) - Nguyen, Thang Huy; Gall, Seana; Cadilhac, Dominique A.; Nguyen, Hoang; Terry, Daniel; Pham, Binh N.; Nguyen, Trung Q.; Nguyen, An T.; Dao, Nha T.; Duong, Chinh D.; Phan, Bau V.; Phan, Hoang T.
Abstract: Background: An essential strategy to reduce mortality and disability after stroke is to ensure access to evidence-based care. In developed countries, it has been shown that if hospitals improve the quality of care, the impact of stroke is attenuated. However, in developing countries, data on the processes of care and associated patient outcomes are scarce. We examined the care processes and outcomes among patients with acute stroke from a stroke unit in a major public hospital in Vietnam whereby there are approximately 15, 000 hospital admissions for stroke per year. Methods: We included first-ever strokes admitted to the 115 People's Hospital (June 2017-March 2018). Data were collected in the Registry of Stroke Care Quality which is used in >50 countries. Baseline characteristics, stroke-related factors (e.g., type and severity), processes of care (e.g., thrombolysis), and outcomes at discharge were examined including mortality and functional outcome, assessed as the walking ability without assistance. Results: Data were available for 6601 patients with first-ever stroke (44% women, 80% ischemic stroke [IS], median age: 62 years, interquartile range [IQR]: 53-72) who received stroke unit care. The median time from stroke onset to hospital arrival was 15.7 hours (IQR: 5.6-37.5). At admission, the median National Institute of Health Stroke Scale score indicating stroke severity was 7 (IQR: 4-12). Among those with IS, 9% received intravenous thrombolysis. Over 90% of the participants received recommended process of care including dysphasia screening (99%), antihypertensive agents (92%), cholesterol-lowering medication (IS = 99%), and antithrombotic medication (IS = 98%). At discharge (median length of stay: 4 days, IQR: 3-6), 3% of all cases died and 46% were able to walk independently. Advanced age, stroke severity, and not receiving antihypertensive agent(s) were contributing factors to mortality and poorer functional outcome. Conclusion: There was a considerable delay in the time from stroke onset to hospital arrival. Evidence-based care at the stroke unit was consistently provided. It remains unclear whether other hospitals in Vietnam and other developing countries perform as well. Greater public awareness of stroke to reduce onset to arrival times and more stroke units are warranted to achieve the excellent outcomes in the major public hospital.